(untitled) (Comprehensive Journal of Science, 2025)
The world is witnessing rapid development in communication technology which has led to the emergence of digital media as one of the most important tools of soft power in the twenty-first century, National security, in its comprehensive sense - political, military, informational, and societal - has become Directly related to digital interactions and the transfer of information via electronic platforms, this research aims to analyze the role that digital media plays in supporting national security through raising awareness and crisis management, it also involves identifying threats, as well as monitoring the risks caused by misuse such as rumors, incitement and digital extremism, This research concludes that digital media is a double – edged sword, it concludes to supporting national security by enhancing public awareness. However, it can pose a threat when used to spread rumors, incitement and psychological warfare, therefore, its positive use requires wise management, the development of national strategies, and integrated media and security policies to ensure the protection of national security.